Relationships among Functional Health Literacy, Asthma Knowledge and the Ability to Care for Asthmatic Children in Rural Dwelling Parents - Evelyn L. Hoover; Carolyn S. Pierce; Gale A. Spencer; Mary X Britten; Martha Neff-Smith; Gary D James; Sarah H. Gueldner (Rural Nurse Organization; Binghamton University, 2012)
Purpose: This Orem-based study examined the relationships among functional health literacy, asthma knowledge, the ability to care for asthmatic children and sociodemographic factors among rural parent/guardians. Method: A descriptive correlation design was used. The convenience sample of 57 parents and one guardian who cared for asthmatic children was recruited from three rural health districts in the eastern United States (Virginia, North Carolina, and upstate New York). Subjects completed the Test of Functional Health Literacy in Adults (TOFHLA) and the Asthma Questionnaire-Parent Survey (AQ-P) and provided additional demographic and health status information. Findings: The results show that TOFHLA scores were directly related to asthma knowledge (AQ-P scores), p=.04.  Subjects who had not completed high school had significantly lower TOFHLA scores than those who had completed high school, and their children were hospitalized more often (p=.05). Those with higher income also had higher health literacy (TOFHLA scores) (p=.008) and regression analysis revealed that smoking status was also directly associated with functional health literacy (p=.004). Conclusions: The findings confirm that rural health care providers need to be diligent in assuring that health education materials and verbal instructions are presented in the most simple and easy to read format in order to maximize understanding.   Keywords: Health Literacy, Asthma Knowledge, Orem's Theory of Dependent Care Agency